Analysis of PISA Model Problems on Junior High School Mathematics Textbooks Published by Indonesia Ministry of Education in the 2017 Revised Edition - Ardy, Hafizatul; Susanta, Agus; Zamzaili, Zamzaili; Susanto, Edi (Jurnal Pendidikan MIPA, 2023)
This study aims to describe the problems of the PISA model in mathematics textbooks which are in terms of the aspects contained in the components of the PISA model. The research subjects were competency test questions in the 2017 revised edition of the 2017 curriculum 2013 math textbooks, totaling 180. This study used a descriptive method with a qualitative approach. The research instrument was an analysis guide sheet based on the aspects of content, context, and cognitive level of the PISA model questions. Data analysis uses the stages of unit purchasing analysis, categorizing, and coding. The results showed that there were 17.22% of the PISA model questions. The questions are distributed based on each content consisting of number, space & shape, change & relationship, and impossibility & data. In the context aspect, the questions only fulfill three contexts, personal work, and social judging from the level of cognitive questions that are applied at the level of remembering, understanding, applying, analyzing, and assessing levels. Keywords: mathematics textbook, PISA model, junior high school.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp213-224